Preserving Historical Structures, Motivations of Property Owners, and the Effects on Community Socio-Economic Renewal in Japan - Deryk Cameron Bliss (Environmental Science and Sustainable Development)
Japan, perhaps more than any nation, embodies the issues and contradictions surrounding depopulation and its subsequent effects on rural communities, including the conservation of a locality’s traditional vernacular architecture and the cultural practices associated with their construction and preservation. Official programs aimed at revitalization of the Japanese countryside or smaller regional centers have proven ineffective, largely due to funding or a reliance on “return to hometown” programs aimed at retirees or a small number of the working-age cohort wishing to pursue an alternative to urban lifestyles.  As a result, these communities have continued to rapidly decline, resulting in an estimated 8 million abandoned or underutilized buildings throughout the country, including perhaps up to 1 million extant vernacular-built heritage structures.  The loss of these structures and their attendant use values, artisanal techniques and practices used in their construction and maintenance, as well as the more intangible aspects of their presence in a community, represents a profound challenge which evades simple solutions.  Adaptive reuse, or the renovation or rehabilitation of built structures for new purposes, may present the most comprehensive strategy through which a variety of stakeholders may arrest or at least slow these processes.  By examining the motivations of, and obstacles faced by, a small but growing group of enthusiasts undertaking rehabilitation projects of these built heritage structures, a new, more grassroots-based revitalization strategy can be elucidated and exported to similarly challenged communities.